2020
DOI: 10.3389/fmicb.2020.574054
|View full text |Cite|
|
Sign up to set email alerts
|

Potent Restriction of Sexual Zika Virus Infection by the Lipid Fraction of Extracellular Vesicles in Semen

Abstract: Sexual Zika virus (ZIKV) transmission from men to women occurs less frequently than the often-detected high viral loads in semen would suggest, but worries that this transmission route predisposes to fetal damage in pregnant women remain. To better understand sexual ZIKV pathogenesis, we studied the permissiveness of the human female genital tract to infection and the effect of semen on this process. ZIKV replicates in vaginal tissues and primary epithelial cells from the vagina, ectocervix, and endocervix and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 82 publications
1
8
1
1
Order By: Relevance
“…There is scarce data explaining the mechanisms underlying viral synergism; to the best of our knowledge, only one study explored HSV-ZIKV coinfection and the cellular model was first-trimester trophoblastic cells (Aldo et al, 2016), which are not typical host cells for HSV. In these cells derived from placenta, the authors showed that ZIKV is cytotoxic and blocks type I interferon signaling; in contrast, we did not observe cytopathic effects in our model of primary epithelial cells from the female tract (Wang R. et al, 2020), Thus, there is a gap of knowledge in regards to the pathogenesis of ZIKV in genital tissues. Because HSV-2 infection induces cellular changes that could both enhance (e.g., induction of entry receptors, disruption of the monolayer architecture) and inhibit ZIKV infection (e.g., upregulation of immune factors like IL-8 and IL1β), we tested whether acute infection with HSV-2 alters the susceptibility of target cells to ZIKV using an in vitro model of ZIKV challenge.…”
Section: Introductioncontrasting
confidence: 72%
See 3 more Smart Citations
“…There is scarce data explaining the mechanisms underlying viral synergism; to the best of our knowledge, only one study explored HSV-ZIKV coinfection and the cellular model was first-trimester trophoblastic cells (Aldo et al, 2016), which are not typical host cells for HSV. In these cells derived from placenta, the authors showed that ZIKV is cytotoxic and blocks type I interferon signaling; in contrast, we did not observe cytopathic effects in our model of primary epithelial cells from the female tract (Wang R. et al, 2020), Thus, there is a gap of knowledge in regards to the pathogenesis of ZIKV in genital tissues. Because HSV-2 infection induces cellular changes that could both enhance (e.g., induction of entry receptors, disruption of the monolayer architecture) and inhibit ZIKV infection (e.g., upregulation of immune factors like IL-8 and IL1β), we tested whether acute infection with HSV-2 alters the susceptibility of target cells to ZIKV using an in vitro model of ZIKV challenge.…”
Section: Introductioncontrasting
confidence: 72%
“…We previously established primary, oncogene-untransformed epithelial cell lines from benign tissues of the vagina, ectocervix, and endocervix, and demonstrated that they can be productively infected by both ZIKV and HSV-2 ( Gornalusse et al, 2020 ; Wang R. et al, 2020 ). To investigate whether infection with HSV-2 impacts ZIKV replication, we infected epithelial cell lines with HSV-2 at an MOI of 0.1 for 24 h prior to adding ZIKV virions at an MOI of 1.0 for 1.5 h. Cells were washed, then genome copies of ZIKV bound to or taken up by cells was measured with quantitative RT-PCR.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Earlier reports have shown that semen EVs from healthy human contained antiviral factors, such as host restriction factors (HRFs) mRNAs, and specifically increased resistance to HIV replication and spread ( Madison et al, 2014 , 2015 ); so did the EVs derived from symbiotic vaginal lactobacilli ( Ñahui Palomino et al, 2019 ). Meanwhile, the semen EVs with a special lipid fraction are also able to restrict ZIKV transmission ( Wang et al, 2020 ). In the process of suppressing HCV infection, the EVs derived from macrophages or umbilical cord mesenchymal stem cells (UMSC) are an appropriate choice ( Qian et al, 2016 ; Cai et al, 2018 ; Khatri et al, 2018 ).…”
Section: Diagnosis and Treatment Of Virus-related Diseases Based On Extracellular Vesiclesmentioning
confidence: 99%